2000
DOI: 10.1094/cchem.2000.77.6.779
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Polylactic Acid Starch‐Based Loose‐Fill Packaging Foams

Abstract: In this study, attempts were made to improve the characteristics of starch‐based plastic foams by blending starch with polylactic acid (PLA), a biodegradable polymer made from renewable sources. Formulations of the foams (types of starch, ratio of starch to polymer, and moisture content) were optimized. Physical and mechanical properties of the foams, including expansion, unit density, bulk density, water solubility index (WSI), spring index, and compressibility on both single piece and bulk samples were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 8 publications
1
56
0
Order By: Relevance
“…A cylindrical aluminum container with a volume of 365 cm 3 (6.93 cm in diameter and 9.68 cm in depth) was used to confine the bulk samples. [24] The forces required to initially compress the samples to 80% of their original volumes and the forces required to recompress the same samples 1 min after releasing the initial load were recorded. BSI was calculated by dividing the recompression force by the initial compression force and has an ideal value of 1.…”
Section: Bulk Spring Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…A cylindrical aluminum container with a volume of 365 cm 3 (6.93 cm in diameter and 9.68 cm in depth) was used to confine the bulk samples. [24] The forces required to initially compress the samples to 80% of their original volumes and the forces required to recompress the same samples 1 min after releasing the initial load were recorded. BSI was calculated by dividing the recompression force by the initial compression force and has an ideal value of 1.…”
Section: Bulk Spring Indexmentioning
confidence: 99%
“…It was calculated by dividing the peak force required to compress (deform) the sample by 80% [to 20% of their original dimension (diameter)] by the initial axial cross-sectional area of the foams. [24] A mean value was obtained by averaging five replicates.…”
Section: Bulk Compressibilitymentioning
confidence: 99%
“…Fang et al . 2) also reported that the addition of PLA improved the physical and mechanical properties of starch based foams. Ke et al .…”
mentioning
confidence: 92%
“…Fang et al . 2) reported the unit density of the extrudates with 40% PLA was about 40 kg m 3 . An addition of 0.25% CAN and 25% PLA gave a bulk density similar to that of 40% PLA without CAN.…”
mentioning
confidence: 99%
“…Starch has been traditionally being widely used as a major low-cost food item in many countries. Due to its low-toxicity, abundant availability, biodegradable, and low cost, starch and its derivatives are widely used in various industry applications such as coating and sizing in paper industries, binder and adhesives, absorbent, drug delivery carriers, and implants [3][4][5][6]. However, the inherent poor mechanical properties, insolubility in water, and high viscosity have limited the utilization of native starch in various applications.…”
Section: Introductionmentioning
confidence: 99%